Analisis Hukum Terhadap Tindak Pidana Kekerasan Seksual - Asmah; Dian Eka Kusuma Wardani (Kertha Wicaksana, 2023)
Harassment is often perceived as deviant behavior, because the act forces someone to engage in a sexual relationship or establishes someone as an object of unwanted attention. That is, sexual harassment can be in the form of indecent behavior, such as touching vital body parts, or it can only be in the form of words or statements that are indecent. The method used in this research is normative research based on primary legal materials, secondary legal materials and tertiary legal materials. The technique used in collecting data is library research. And then analyzed descriptively. The results of this study indicate that sexual violence crimes consist of: a. non-physical sexual harassment, b. physical sexual harassment, c. forced contraception; d. forced sterilization; e. forced marriage; f. sexual abuse; g. sexual exploitation; h. sexual slavery; and i. electronic based sexual violence. Sexual Violence Crimes also include a. rape; b. obscenity; c. intercourse with children, obscene acts against children, and/or sexual exploitation of children; d. acts of violating decency that are contrary to the will of the victim; e. pornography involving children or pornography that explicitly contains violence and sexual exploitation; f. forced prostitution; g. criminal acts of trafficking in persons aimed at sexual exploitation; h. sexual violence within the household; i. money laundering crime whose predicate crime is a crime of sexual violence; j. other criminal acts that are expressly stated as criminal acts of sexual violence as regulated in the provisions of laws and regulations. The impact of violence on victims includes the following impact on physical or psychological health, impact on fulfilling women's human rights and social relations and economic impact.